2022
DOI: 10.14202/vetworld.2022.2715-2724
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mulberry (Morus alba Linn.) leaf supplementation on growth performance, blood parameter, and antioxidant status of broiler chickens under high stocking density

Abstract: Background and Aim: A stocking density system in boilers is well known for increasing productivity. However, this system increases stress and affects the growth performance of broilers. Mulberry is a valuable plant with therapeutic applications in traditional medicine; moreover, it reduces free radicals and improves growth performance in broilers. This study was conducted to investigate the effects of mulberry on the blood biochemistry parameters and the antioxidant status of broilers exposed to various raisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The glutathione peroxidase (GPx) activity was calculated using the GSSG concentration of the supernatant, which was obtained after centrifuging the reaction mixture for 15 min at 350 g . Based on a GPx unit of mmol(s) of GSSG formed/min at pH 7.4 and 30 °C ( 30 ), the protein results were expressed as a unit/mg.…”
Section: Methodsmentioning
confidence: 99%
“…The glutathione peroxidase (GPx) activity was calculated using the GSSG concentration of the supernatant, which was obtained after centrifuging the reaction mixture for 15 min at 350 g . Based on a GPx unit of mmol(s) of GSSG formed/min at pH 7.4 and 30 °C ( 30 ), the protein results were expressed as a unit/mg.…”
Section: Methodsmentioning
confidence: 99%
“…their livestock: cattle [226], chicken [227], fi sh [228], sheep [229], pigs [230], and rabbits [231], and these are some of the recent and much selected examples.…”
Section: Analysis or Production Methods Referencesmentioning
confidence: 99%
“…Additionally, no new eligible studies were identified by reviewing the reference lists of relevant articles. Finally, a total of 18 studies were included in the meta-analysis [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…Several studies have investigated the effects of a mulberry leaf diet on various poultry and livestock, however, their results have been inconsistent [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Moreover, no systematic review has yet summarized the effects of mulberry leaves on the growth, production performance, gut microbiota, and immunological parameters of poultry and livestock.…”
Section: Introductionmentioning
confidence: 99%